1987
DOI: 10.1016/0306-4522(87)90067-4
|View full text |Cite
|
Sign up to set email alerts
|

The development of changes in hippocampal GABA immunoreactivity in the rat kindling model of epilepsy: A light microscopic study with gaba antibodies

Abstract: Immunocytochemical techniques were used to study changes of GABA immunoreactivity in the rat hippocampal CA1 region during kindling epileptogenesis, gradually developing over a period of two weeks by daily electrical tetanization of Schaffer collaterals/commissural fibres. The number of GABA-immunoreactive somata per mm2 was quantified in CA1 region after 6 and 14 stimulus-induced afterdischarges and in fully kindled animals. The absolute values were compared with those obtained from controls and the relative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1989
1989
2007
2007

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Many previous neurophysiological studies have indicated that a failure of inhibition is a principal reason for neuronal hyperexcitability during epileptic seizures (Gean et al, 1989;Kamphuis et al, 1987;Kapur et al, 1989;Morimoto et al, 1987a,b;Ribak, 1991). Gammaaminobutyric acid (GABA) is the major inhibitory neurotransmitter in the central nervous system.…”
Section: Introductionmentioning
confidence: 99%
“…Many previous neurophysiological studies have indicated that a failure of inhibition is a principal reason for neuronal hyperexcitability during epileptic seizures (Gean et al, 1989;Kamphuis et al, 1987;Kapur et al, 1989;Morimoto et al, 1987a,b;Ribak, 1991). Gammaaminobutyric acid (GABA) is the major inhibitory neurotransmitter in the central nervous system.…”
Section: Introductionmentioning
confidence: 99%
“…This induces a progressive and permanent decrease in seizure threshold, which usually is apparent as increasing intensities of convulsive responses to successive, initially subconvulsive, stimuli (Goddard et al 1969). There has been disagreement on what happens to inhibition with kindling, but a combination of recent anatomical and physiological studies suggests that after an initial transient increase, GABA-mediated inhibition progressively weakens as the kindling develops (Morimoto & Goddard, 1986; Kamphuis, Wadman, Buijs & Lopes da Silva, 1987;Maru & Goddard, 1987 a; Kamphuis, Lopes da Silva & Wadman, 1988), perhaps as a result of plastic changes involving NMDA receptors (Stelzer, Slater & Ten Bruggencate, 1987).…”
Section: Chronic Subacute and Clinical Epilepsiesmentioning
confidence: 99%
“…g-Aminobutyric acid (GABA)ergic transmission may also be important in TLE, as GABAergic interneurons seem to be involved in kindling-induced plasticity changes in the amygdala (Kamphuis et al, 1987;Callahan et al, 1991) and activation of kainate receptors modulates GABAergic synaptic transmission in the amygdala (Braga et al, 2003). Therefore, the aim of this study was to investigate whether the activation of GLU K5 kainate receptors and/or inactivation of GABA A receptors can rescue the kindling-induced impairment of LA-LTP.…”
Section: Introductionmentioning
confidence: 99%